2010
DOI: 10.1557/jmr.2010.0290
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability and Raman scattering of InN nanowires under high pressure

Abstract: High-pressure in situ angular dispersive x-ray diffraction study on the wurtzite-type InN nanowires has been carried out by means of the image-plate technique and diamond-anvil cell (DAC) up to about 31.8 GPa. The pressure-induced structural transition from the wurtzite to a rocksalt-type phase occurs at about 14.6 GPa, which is slightly higher than the transition pressure of InN bulk materials ($12.1 GPa). The relative volume reduction at the transition point is close to 17.88%, and the bulk modulus B 0 is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
4
18
2
Order By: Relevance
“…[4][5][6][7] Pinquier and coworkers 4,5 investigated the pressure dependence of the E 2h , A 1 (TO), and LO phonons of w-InN. Pressure coefficients and mode Grüneisen parameters were obtained for these phonon modes, and the wurtzite-to-rocksalt transition was found to lie in the 12-14 GPa range, in agreement with x-ray diffraction measurements 8 and with the predictions of ab initio calculations.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…[4][5][6][7] Pinquier and coworkers 4,5 investigated the pressure dependence of the E 2h , A 1 (TO), and LO phonons of w-InN. Pressure coefficients and mode Grüneisen parameters were obtained for these phonon modes, and the wurtzite-to-rocksalt transition was found to lie in the 12-14 GPa range, in agreement with x-ray diffraction measurements 8 and with the predictions of ab initio calculations.…”
Section: Introductionsupporting
confidence: 55%
“…5,6 This can be observed in Fig. 5 for the case of sample C. In the spectrum obtained at 12.1 GPa, it can be seen that the phonons of w-InN coexist with new bands that are assigned to rs-InN.…”
Section: Raman Scattering In Rs-innmentioning
confidence: 66%
See 2 more Smart Citations
“…Recently, Yao and co-workers employed Raman scattering to investigate the structural stability of poorly crystalline w-InN nanowires under high pressure. 9 The pressure coefficients and mode Grüneisen parameters obtained by these authors for the A 1 (TO), E 2h , and A 1 (LO) modes were sizably lower than those reported in Refs. 7 and 8.In this letter, we present Raman-scattering measurements under high hydrostatic pressure on high-quality c-face and a-face InN epilayers grown by MBE.…”
contrasting
confidence: 57%